Effect of health education in the control of schistosomiasis in Dass Emirate Council of Bauchi State, Nigeria: An intervention study. - Sunday Charles Adeyemo; Gbadebo Jimoh Oyedeji; James Atolagbe; Oladunni Opeyemi; Sunday Olarewaju; Calistus Akinleye; Funso Olagunju; Eniola Dorcas Olabode; Abdulwaris Salisu Maleka (PLoS Neglected Tropical Diseases)
Objective Schistosomiasis has been recognized by WHO as a major contributor to mortality and morbidity, particularly in Sub-Sahara Africa, where it is most prevalent. There is a lack of reliable data on the effectiveness of health education interventions in reducing the prevalence of schistosomiasis in Bauchi State. Hence, the study assessed the prevalence of schistosomiasis and the knowledge, attitude and practices of community members of Dass Emirate towards the prevention and control of schistosomiasis before and after health education intervention. Results At pre-intervention, the majority of the respondents 234 (66.9%) have been diagnosed, or have family members or community members who have been diagnosed with schistosomiasis. Ninety-six (27.5%) of respondents have good knowledge about schistosomiasis. 79 (22.6%) of the respondents strongly agree that they can confidently recognize symptoms of schistosomiasis. Only 91 (26.0%) strongly agreed to taking responsibilities for taking preventive measures. At post-intervention, the prevalence of schistosomiasis dropped to 55.1%. This was statistically significant at p = 0.043 using McNemar's test as a test of significance. Knowledge about schistosomiasis increased from 27.5% to 87.0% at post-intervention. This was statistically significant at p <0.05. Regarding attitudes and practices, good attitudes and practices increased from 59.1% at pre-intervention 71.0% at post-intervention. However, this was not statistically significant (p>0.05). Health education and education level of respondents were predictors of Knowledge, Attitude and Practices scores.